Healthy Brownies Formulation with Durian Seed Flour Substitution and Dragon Fruit Peel as a Nutritious Food Alternative for School-Age Children - Azizah, Faulina Luthfi; Nuraeni, Indah; Ramadhan, Gumintang Ratna; Wijayanti, Nur (Jurnal Ilmu Kesehatan (JIKSAN), 2025)
Background: Durian seeds are a potential food ingredient to substitute wheat flour due to their nearly equivalent carbohydrate content, which is 72.73%. Additionally, dragon fruit peel contains a high fiber content of 47.7% and a significant amount of phenolic antioxidants, amounting to 39.7±5.39 mg GAE/100 g. School age is a critical period for children's optimal growth and development, which must be supported by adequate nutritional intake. One effort to support this is by modifying snacks, such as brownies, using durian seed flour substitution and the addition of dragon fruit peel to enhance their nutritional quality. Purpose: This study aims to investigate the effect of durian seed flour substitution and the addition of dragon fruit peel on the organoleptic quality and nutritional content of brownies, and to determine the best formulation suitable for school-age children. Method: This research employed an experimental method using a Randomized Block Design (RBD). The treatments included the addition of 30 g of dragon fruit peel pulp and substitution of durian seed flour at 15%, 30%, and 45%. Organoleptic tests were conducted using the Friedman test followed by Duncan’s Multiple Range Test. The best formula was determined through the Effectiveness Index test and was further analyzed for its nutritional content, including protein, carbohydrates, fat, crude fiber, and phenolics. Result: The hedonic organoleptic test results showed that all treatments—D1N (15% durian seed flour: 85% wheat flour + 30 g dragon fruit peel), D2N (30%:70% + 30 g), and D3N (45%:55% + 30 g)—had significant differences in aroma and texture quality. The best formula was found in D1N treatment, which used 15% durian seed flour and 30 g of red dragon fruit peel pulp. This formulation contained 24.90% fat, 1.80% protein, 46.97% carbohydrates, 3.241% crude fiber, and 1,340 mg of phenolic conten